Hall–Petch Slope in Ultrafine Grained Al-Mg Alloys - Zhou, D.; Wang, H.; Saxey, David; Muránsky, O.; Geng, H.; Rickard, William; Quadir, Z.; Yang, C.; Reddy, Steven; Zhang, D. (SPRINGER, 2019)
The Hall–Petch relation has long been used to relate the yield strength of a metal to its grain sizes in which the effectiveness of grain size strengthening in the metal is dictated by the Hall–Petch coefficient (slope). Therefore, understanding the microstructural dependence of the Hall–Petch slope would be very useful in designing new high-strength ultrafine grained (UFG) metallic materials. In this study, we investigated the microstructural factors affecting the Hall–Petch slope in UFG Al-Mg alloys with an average grain size range from 374 to 639 nm and different Mg contents of 0, 2.5, 5, and 7.5 at. pct. The rods prepared by extrusion of mechanically alloyed powder compacts were annealed for 5 hours at 380 °C, 420 °C, and 500 °C respectively followed by water quenching to produce the alloy samples in this study. The measured Hall–Petch slopes of the samples were found to increase with increasing Mg content and had higher values than those previously reported for Al(Mg) solid solutions with Mg concentrations comparable to the Mg contents in this study. Analysis of X-ray diffraction, transmission electron microscopy, and atom probe tomography experimental data as well as strengthening mechanisms demonstrates that the formation of nanoscale MgO dispersions plays a major role in the improved Hall–Petch slope observed in Al-Mg alloys.